Pengaruh Rasio Profitabilitas, Ukuran Perusahaan, Struktur Modal, dan Kebijakan Dividen Terhadap Nilai Perusahaan - Angelina Irena; RM Rum Hendarmin; Reny Aziatul Pebriani (Jurnal Pendidikan Akuntansi (JPAK), 2023)
This study aims to empirically prove the effect of profitability ratio, company size, capital structure, and dividend policy on company value. The method used in selecting research samples is purposive sampling technique. The sample of this study was 19 food and beverage companies listed on the IDX from 2019 to 2021 with a 3-year observation period of 57 company samples. The data analysis model used in this study is a multiple linear regression analysis model with a tool in the form of statistical software known as SPSS 26. The results of this study show that (1) the profitability ratio (X1), company size (X2), capital structure (X3), and dividend policy (X4) simultaneously have a positive and significant effect on the value of the company; (2) the profitability ratio (X1) has a positive and significant effect on the value of the company (PBV); (3) the size of the company (X2) has no positive and significant effect on the value of the company (PBV); (4) capital structure (X3) positively and significantly affects the value of the company (PBV); (5) dividend policy (X4) has no positive and significant effect on the value of the company (PBV).